(untitled) (Scientia Agricola, 2009)
To further understand the impact of tillage on CO2 emission, the applicability of two conceptual models was tested, which describe the CO2 emission after tillage as a function of the non-tilled emission plus a correction due to the tillage disturbance. Models assume that C in readily decomposable organic matter follows a first-order reaction kinetics equation as: dCsoil (t) / dt = -k Csoil (t), and that soil C-CO2 emission is proportional to the C decay rate in soil, where Csoil(t) is the available labile soil C (g m-2) at any time (t) and k is the decay constant (time-1). Two possible assumptions were tested to determine the tilled (F T) fluxes: the decay constants (k) of labile soil C before and after tillage are different (Model 1) or not (Model 2). Accordingly, C flux relationships between non-tilled (F NT) and tilled (F T) conditions are given by: F T = F NT + a1 e-a2t (model 1) and F T = a3 F NT e-a4t (model 2), where t is time after tillage. Predicted and observed CO2 fluxes presented good agreement based on the coefficient of determination (R² = 0.91). Model comparison revealed a slightly improved statistical fit of model 2, where all C pools are assigned with the same k constant. Rotary speed was related to increases in the amount of labile C available and to changes of the mean resident labile C pool available after tillage. This approach allows describing the temporal variability of tillage-induced emissions by a simple analytical function, including non-tilled emission plus an exponential term modulated by tillage and environmentally dependent parameters.